(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research discusses how to enhance and activate the modern tasks and roles of the internal auditor related to helping organizations achieve its goals in terms of (governance, risk management, internal control) and providing exceptional services to management, as well as adding value to the organization as a whole, by adopting creative methods in terms of the basic components of creativity, As the internal auditor’s carrying out these tasks greatly contributes to the success of the financial and administrative work and reaching satisfactory results for all parties, The research problem raised questions about the nature of the role between research variables, and the researchers adopted a scientific approach using the descriptive analytical approach and using the statistical program (spssv23) to find percentages The duplications and the analysis of the nature of the relationship, and a questionnaire form was built, tested, and then distributed to the research sample, and the research reached several conclusions, the most important of which are: The components of creativity have a large and important positive role in improving and distinguishing the performance of internal auditors in relation to achieving the objectives of the organization, helping the administration to carry out its tasks and increase the value The organization through the development and evaluation of services, and research recommends organizations to focus and collaborate between components, Creativity and the work of internal auditors to activate his modern roles.